Single Enema Fecal Microbiota Transplantation in Cats With Chronic Enteropathy - Dimitra A. Karra; Jan S. Suchodolski; Shelley J. Newman; Evgenia Flouraki; Jonathan A. Lidbury; Joerg M. Steiner; Panagiotis G. Xenoulis (Journal of Veterinary Internal Medicine)
ABSTRACT Background Chronic enteropathies (CE) are common in cats, and alterations of the intestinal microbiota might be involved in the pathogenesis. Hypothesis/Objectives To evaluate the efficacy of a single enema fecal microbiota transplantation (FMT) in improving intestinal dysbiosis and clinical scores in cats with CE. Animals Twenty‐eight cats with either chronic inflammatory enteropathy (CIE; n = 19) or small cell gastrointestinal lymphoma (SCGL; n = 9) were prospectively enrolled. Methods Eleven cats were randomly selected to receive a single enema FMT (FMT‐group), and 17 cats were used as controls. Clinical activity was determined using the Feline Chronic Enteropathy Activity Index (FCEAI), and intestinal dysbiosis was determined using the feline dysbiosis index (DI) on the day of FMT (T0) and 30 days after FMT (T1). Results At T0, 14/28 cats had an abnormal DI > 0. No significant difference was found in the DI from T0 to T1 in the FMT group (mean[SD]: 0.01[2.5] vs. 0.7[2.1]; p = 0.47). No significant difference was found in the DI between the FMT group and the control group at T1 (mean[SD]: −0.7[2.1] vs. 0.8[1.8]; p = 0.92). FCEAI significantly decreased at T1 compared to T0 in the FMT group (median[IQR] 10.0[7.7–11.3] vs. 4.5[4–5]; p = 0.002). No significant difference was found in the FCEAI between the FMT group and the control group at T1 (median[IQR] 4.5[4–5] vs. 4[3–5.75]; p = 0.64). Conclusions In this study, single enema FMT did not lead to a significant improvement in DI or FCEAI in cats with CE compared to controls.